PENEGAKAN KHILAFAH DALAM POSTER AKSI “MUJAHID” 212 (Analisis Semiotik Model Roland Barthes) - Mochammad Irfan Achfandhy (Al-MUNZIR, 2020)
Poster is a communication, publication or announcement media that contains several elements such as text, pictures, or a combination of both, with the aim of providing information to the public. But in a poster there is a sign containing implied meaning,like a group ideology.  This study purposes to analyze the sign and construct implied meaning that cannot be clearly displayed on the poster and use a semiotic analysis. This analysis uses Roland Barthes's semiotic model which covers aspects of the first, second and mythologi significance of the marking. This study uses a descriptive qualitative approach in the presentation of research data. The results of the analysis of the Aksi Mujahid 212 poster showed that there was a hidden vision and mission, the problems that are carried out like the KPK Constitution contained in the poster are only to use the moment. Persaudaraan  Alumni (PA) has the intention to establish the Khilafah as a government system in Indonesia. And the results of this study are expected to contribute ideas and critical thinking to interpret the signs on the poster deeper.Keywords: poster, meaning, action 212